2019
DOI: 10.1016/j.neulet.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of nociceptors and dorsal horn neurons contributes to pain in sickle cell disease

Abstract: Sickle cell disease (SCD) describes a group of disorders associated with a point mutation in the beta chain of hemoglobin. The mutation leads to the creation of sickle hemoglobin (HbS) and causes distortion of erythrocytes through polymerization under low oxygen, resulting in characteristic sickle red blood cells. Vaso-occlusion episodes caused by accumulation of sRBCs results in ischemia-reperfusion injury, reduced oxygen supply to organs, oxidative stress, organ damage and severe pain that often requires hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 109 publications
1
9
1
Order By: Relevance
“…The most prevalent and critical skin receptors relate to pressure, temperature, and pain [1] -the Pacinian corpuscle, [3] thermoreceptor, [4] and nociceptor, [5,6] respectively. All these receptors detect stimuli, measure levels of stimuli, and transmit signals to the brain triggering reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent and critical skin receptors relate to pressure, temperature, and pain [1] -the Pacinian corpuscle, [3] thermoreceptor, [4] and nociceptor, [5,6] respectively. All these receptors detect stimuli, measure levels of stimuli, and transmit signals to the brain triggering reactions.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that these phenomenon were accompanied by increased phosphorylation of mitogen-activated protein kinases, including c-Jun N-terminal kinase, p38 and p44/p42 extracellular signalling-regulated kinase (ERK) in the spinal cords of BERK mice. 65,66 ERK activation increases action potential amplitude of spinal cord dorsal horn neurons leading to hyperexcitability. 67 Valverde et al 68 found elevated level of SP, elevated reactive oxygen species and activated microglial and astrocytic cells with increased glial fibrillary acidic protein in the dorsal horn of the spinal cord of BERK mice.…”
Section: Chronic Painmentioning
confidence: 99%
“… 18 , 19 The reduction in pain has been attributed to suppression of inflammation as well as direct effects on nociceptors and targets within the central nervous system. 20 In some pathological conditions, inhibitors of monoacylglyerol lipase, the enzyme that hydrolyzes 2-AG to arachidonic acid and glycerol, increased the level of 2-AG and reduced hyperalgesia through mechanisms dependent on the cannaboid CB1 and CB2 receptors. 21-25 Although increasing endogenous 2-AG may seem attractive as a strategy for managing pathological pain, 2-AG is also an intermediate in the production of pro-nociceptive lipids.…”
Section: Introductionmentioning
confidence: 99%